Practical Programming in Tcl and Tk, Fourth Edition - Jones, Ken; Welch, Brent (Pearson, 2003)
Practical Programming in Tcl/Tk, 4th edition The Tcl/Tk bestseller fully updated for Tcl 8.4! Authoritative coverage of every Tcl and Tk command in the core toolkits State-of-the-art Tk GUI coverage for Tcl, Perl, Python, and Ruby developers Covers all key Tcl 8.4 enhancements: VFS, internationalization and performance improvements, new widgets, and much more Covers multi-threaded Tcl applications and Starkits, a revolutionary way to package and deploy Tcl applications CD-ROM: Source and binary Tcl/Tk distributions and extensions for Windows®, Linux™, Solaris™, and Macintosh®, plus all code from the book The Tcl/Tk bestseller, now completely updated for Tcl 8.4! The world's #1 guide to Tcl/Tk has been thoroughly updated to reflect Tcl/Tk8.4's powerful improvements in functionality, flexibility, and performance!Brent Welch, Ken Jones, and Jeffrey Hobbs, three of the world1s leading Tcl/Tk experts, cover every facet of Tcl/Tk programming, including cross-platform scripting and GUI development, networking, enterprise application integration, and much more.Coverage includes: Systematic explanations and sample code for all Tcl/Tk 8.4 core commands Complete Tk GUI development guidance-- perfect for developers working with Perl, Python, or Ruby Insider's insights into Tcl 8.4's key enhancements: VFS layer, internationalized font/character set support, new widgets, and more Definitive coverage of TclHttpd web server--written by its creator New ways to leverage Tcl/Tk 8.4's major performance improvements Advanced coverage: threading, Safe Tcl, Tcl script library, regular expressions, and namespaces Whether you1re upgrading to Tcl/Tk 8.4, or building GUIs for applicationscreated with other languages, or just searching for a better cross-platformscripting solution, Practical Programming in Tcl and Tk, Fourth Edition delivers all you need to get results! The accompanying CD-ROM includes source and binary distributionsof Tcl/Tk, Tcl extensions, and tools for Windows 9x/2000/XP, Linux, Solaris,and Macintosh, plus all the code from the book.
Online resource; Title from title page (viewed June 10, 2003)
Keywords: Tk toolkit; Tcl (Computer program language); Tcl (Langage de programmation)